Providing a customer satisfaction model of non-attendance services in the social security organization - Hossein Barzgar; Vahid Sanavi Garoosiyan; ali hossein zadeh (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe purpose of this research is to provide a model of customer satisfaction with non-attendance services in the social security organization. The current research is applicable-developmental in terms of purpose; and descriptive-analytical based on the method. The statistical population of the present study includes the customers of Khorasan Razavi Social Security Organization, which was considered to be 384 people by Cochran's formula, and simple random sampling method was used. The collection tool in this research includes a researcher-made questionnaire derived from the qualitative method. The variable of customer satisfaction with non-attendance services includes 4 dimensions of infrastructures, culture building, reforming structures, and creativity and innovation. The reliability of the research was checked and confirmed by Cronbach's alpha criterion in SPSS software. Lisrel software was used to fit the conceptual model of the research. Confirmatory factor analysis was performed to confirm the final research model. The findings of the research showed that the research model has a suitable fit with the collected data. Also, in order to improve the fit indices of the model, the suggested terms in accordance with the research literature were used, and finally the research model was approved.Extended Abstract                                           IntroductionToday, with the invention of new ways to communicate with customers, new communication and electronic methods and sciences related to information technology should also be used. Because, instead of using traditional communication methods, new information technology and advanced electronic communication methods can be used, which will bring about important changes in the field of information and communication technology and the creation of electronic organizations and governments, expanding the influence of the Internet throughout the world, and the emergence of various internet bases and extensive social networks and new media, the production of advanced software, the development of blogs, electronic publications. In this way, a suitable background can be provided for the development and diversification of service delivery methods (Iglesias et al, 2017). With the ever-increasing expansion of the field of e-commerce, the speed of providing services to customers and the quality of services have also increased, causing companies to have more control over quality components to ensure the accuracy and timeliness of delivery of goods and to be able to respond to the growing needs of customers and satisfy them (Zalkani Andarvar, 2021). Diyanti et al, (2021) state that the satisfaction felt by customers is a comparison of the expectations created by customers about the reliability of the performance that a company can provide. According to Permana & Djatmiko (2018), customer satisfaction is a summary of different intensities of emotional reactions that come from a limited time and duration, and target the basic aspects of the consumption of a product. From the above statement, it can be concluded that consumers have a good evaluation of the service and performance of the product for the satisfaction they get from buying a product or provide services they feel (Nabila et al, 2023). Therefore, the researcher is trying to answer the question: what is the customer satisfaction model of non-attendance services in the social security organization?Theoretical FrameworkCustomer satisfactionTeso & Vilton (1899) define satisfaction as: the reaction of customers to evaluate the perceived difference between the previous expectations or to some extent the ideal performance and the actual performance of the product, which is perceived after consumption. Customer satisfaction is defined as the result of an effective evaluation of a benchmark compared to perceived performance in practice. In other words, if the perceived performance meets expectations, satisfaction has been achieved (Shahab Far, 2017).Non-attendance servicesIt means services that a person can do at any hour of the day and night through the Internet, without referring to the organization (Bidmon, 2016).Mirzaee Azandariani & Arya (2022) investigated the impact of the characteristics of second-hand goods platforms on brand loyalty intentions with the mediating role of customer satisfaction (the case study of Divar and Sheipur platform in Iran). The findings of the research showed that ease of use has a positive and indirect effect on the intentions of brand loyalty with the mediating role of customer satisfaction. Perceived usefulness has a positive and indirect effect on the intentions of brand loyalty with the mediating role of customer satisfaction, and entertainment aspect has a positive and indirect effect on the intentions of brand loyalty with the mediating role of customer satisfaction, and the sense of belonging to the society for a society has a positive and indirect effect on the intentions of brand loyalty with the mediating role of customer satisfaction, and the credibility of the seller on the intention and brand loyalty intentions have a positive and indirect effect as a mediator of customer satisfaction, and knowing the third party has a positive and indirect effect on brand loyalty intentions as a mediator of customer satisfaction.Deylami Moezzi (2021) investigated the presentation of a structural model of the role of brand love in the impact of marketing stimuli on customer satisfaction. The findings of the research indicated that the components of marketing stimuli (product stimulus, pricing stimulus, distribution stimulus, and promotion stimulus, respectively), had the greatest effect on customer satisfaction. The results of the research showed that marketing stimuli have a direct and indirect effect on customer satisfaction. Love for the brand plays a mediating role in the effect of the elements of marketing stimuli on customer satisfaction.Research methodologyThe current research is applicable-developmental in terms of purpose; and descriptive-analytical based on the method. The statistical population of the present study includes the customers of Khorasan Razavi Social Security Organization, which was considered to be 384 people by Cochran's formula, and simple random sampling method was used. The collection tool in this research includes a researcher-made questionnaire derived from the qualitative method. The variable of customer satisfaction with non-attendance services includes 4 dimensions of infrastructures, culture building, reforming structures, and creativity and innovation.Research findingsSPSS software was used to analyze the data of this research, and Lisrel software was used to fit the conceptual model of the research. Confirmatory factor analysis was performed to confirm the final research model. The findings of the research showed that the research model has a suitable fit with the collected data. Also, in order to improve the fit indices of the model, the suggested terms in accordance with the research literature were used, and finally the research model was approved.ConclusionThe current research was conducted with the aim of providing a customer satisfaction model of non-attendance services in the social security organization. This research is consistent with the results of Mirzaee Azandariani & Arya (2022), Deylami Moezzi (2021), Katja et al, (2020), Feng et al, (2020), OriolI et al, (2019), LuisArditto et al, (2019), Rita et al, (2019), Suri (2020), and Ehsani (2020). Suri (2020) showed that there is a significant positive relationship between the quality of electronic services with website design and customer service. In addition, the existence of a significant positive relationship between the quality of electronic services and the security of privacy and the fulfillment of services was also confirmed. Other research results show the impact of electronic service quality on customer satisfaction and trust. According to the results, it can be concluded that in order to increase profitability,, companies can achieve the goal of making customers loyal faster by investing in customer satisfaction and increasing their satisfaction with electronic services.Based on the results of the research, it is suggested that by creative management of knowledge and innovative application, the organization can enable employees to rely on their experiences in organizational issues that require new solutions and help the organization as it grows on the learning path. Innovation is recognized as an important factor in enabling companies to maintain perceived customer value and maintain competitive advantage in a highly complex and rapidly changing environment. Innovation is the key factor in the success or failure of organizations in the field of competition and the main source of competitive advantage. However, with the increasing opportunities offered by technology and artificial intelligence, digital assistants can create favorable outcomes for Social Security clients with new services.